Carbon and water vapor balance in a subtropical pine plantation - Posse Beaulieu, Gabriela (2016)
Afforestation has been proposed as an effective tool for protecting primary and/or secondary forests and for mitigating atmospheric CO2. However, the dynamics of primary productivity differs between plantations and natural forests. The objective of this work was to evaluate the potential for carbon storage of a commercial pine plantation by determining its carbon balance. Measurements started when trees were aged 6 and ended when they were older than 8 years. We measured CO2 and water vapor concentrations using the Eddy covariance method. Gross primary productivity in 2010 and 2011 was 4290 ± 473 g C m-2 and 4015 ± 485 g C m-2, respectively. Ecosystem respiration ranged between 7 and 20 g C m-2 d-1, reaching peaks in all Februaries. Of the 30 months monitored, the plantation acted as carbon source for 21 months and as carbon sink for 6 months, while values close to neutrality were obtained during 3 months. The positive balance representing CO2 loss by the system was most likely due to the cut branches left on the ground following pruning activities. The plantation was subjected to pruning in January and September 2008 and to sanitary pruning in October 2010. In all cases, cut branches were not removed but remained on the ground. Residue management seems to have a very important impact on carbon balance.